El hábito de fumar : un factor de riesgo en la enfermedad periodontal (1996)
ABSTRACT: It has been proved through a large number of clinical research and observations, that the smoking habit, constitutes an important risk factor in the prevalence and severity of a large number of systemic, oral and periodontal diseases. This bibliographic review will try to show the effect of tobacco use in relation to the periodontal disease and its treatment, emphasizing the important role of the dentist in prevention of this habit.